Resistance to deltamethrine in two populations of Aedes aegypti (Diptera, Culicidae) from Peru - Chávez, Julio (2005)
The objective of the present work was to determine the resistance levels to deltamethrine in two populations of Aedes aegypti from Peru. Bioassays in adults were carried out following the methodology of the World Health Organization. We met resistance in the Sullana population with 70% of mortality and susceptibility in the population The Future El Porvenir with 99% of mortality.